The Effect of Interactive Digital Learning Module on Student’s Learning Activity and Autonomy - Tarigan, Wenny Pinta Litna; Sipahutar, Herbert; Harahap, Fauziyah (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2021)
In the modern society, the internet breaks through the restrictions on time and space and becomes a ubiquitous learning tool. Designing teaching activity for digital learning and flexibly applying technology tools are the key issues for current information technology integrated education. Interactive learning modules could be used in the classroom environment for effective learning. This study explored the effect of instructional modules for providing supplementary instruction in biology concepts. Interactive digital learning module was developed in order to assist students in biology learning. Interactive activities were considered in this study, include teacher – student interaction, student - student interaction, student - content interaction, and student - technology interaction. 180 students of Grade 11 in 6 classes at SMAN 2 Balige were selected as the research subjects. Three groups of students participated in biology learning course, (2 classes) using different modules were interactive digital module, digital module and text module. Goal of this research was to determine the impact of interactive digital learning module on students’ learning activity and autonomy. Quantitative results obtained by using questionnaire to understand the student’s learning activity and autonomy. Results showed student’s activities and autonomy who learned with interactive digital learning modules significantly different with students who learned using text learning modules. The use of interactive features increased the activity and autonomy of learners and created the student-centered learning environment. Students under interactive multimedia instruction performed better than text module class. These findings suggested that learning activity and autonomy of students in biology could be enhanced by multimedia instruction.